The role of nitric oxide and autophagy in liver injuries induced by selenium deficiency in chickens. Issue 62 (8th July 2015) - Liu, Chunpeng; Fu, Jing; Liu, Ci; Li, Shu
<x xml:space="preserve">Abstract</x> Selenium (Se) is recognized as a necessary trace mineral in animal diets, including those of birds.